Teaching Simple Strategies to Foster Emotional Well-Being - Iovino, Emily A.; Koslouski, Jessica B.; Chafouleas, Sandra M. (Frontiers in Psychology, 2021)
The COVID-19 pandemic has presented considerable disruptions to routines that have challenged emotional well-being for children and their caregivers. One direction for supporting emotional well-being includes strategies that help children feel their best in the moment, which can bolster their capacity to respond appropriately to thoughts and behaviors. Strengthening emotional well-being equitably, however, must include opportunities in settings that are easily accessible to all, such as schools. In this paper, we focus on simple, evidence-informed strategies that can be used in schools to promote positive feelings in the moment and build coping behaviors that facilitate tolerance of uncertainty. We focus on those strategies that educators can easily and routinely use across ages, stages, and activities. Selected strategies are primarily tied to cognitive-behavioral theory, with our review broadly organized across categories of self-awareness, self-soothing, and social relationships.  We review evidence for each, providing examples that illustrate ease of use in school settings.